For the first question about Jason's solution to the quadratic equation \( x^2 - 4x - 12 = 0 \):
- Step 1: He correctly writes the equation.
- Step 2: The factorization (x - 6)(x + 2) is incorrect. The correct factorization should be (x - 6)(x + 2) = 0, which actually leads to the solutions \( x = 6 \) and \( x = -2 \). Therefore, Jason's first mistake occurs in Step 2.
So the correct response is Step 2.
Now for the second question regarding solving \( x^2 + 3x - 10 = 0 \) by factoring:
To factor \( x^2 + 3x - 10 \), we look for two numbers that multiply to -10 and add to 3. Those numbers are 5 and -2.
The factorization is: \[ (x + 5)(x - 2) = 0 \]
Setting each factor to zero gives:
- \( x + 5 = 0 \) → \( x = -5 \)
- \( x - 2 = 0 \) → \( x = 2 \)
Thus, the solutions are \( x = -5 \) and \( x = 2 \).
The correct responses are:
- \( x = -5 \)
- \( x = 2 \)
Therefore, the correct answers are x = -5 and x = 2.